Pyrolysis and combustion of sugarcane bagasse - Morais, L. C. [UNESP]; Maia, A. A.D. [UNESP]; Guandique, M. E.G. [UNESP]; Rosa, A. H. [UNESP] (Springer Nature, 2017)
The inadequate and indiscriminate disposal of sugarcane bagasse (SCB) has received much attention. The exploration of bioenergy properties of biomasses and its biochars play an important role in achieving their utilization. In this context, understanding thermal conversion processes of biomass and biochars it is crucial to use them at bioenergy production. The aim of this study was to investigate thermal behavior of SCB biomass residue, as well as his biochar, by thermogravimetric analysis (TG), including thermodynamic parameters for non-isothermal analyses using Ozawa–Flynn–Wall (OFW), Kissinger–Akahira–Sunose (KAS) and Friedman, kinetic isoconversional methods. Thermal analyses were conducted under oxidative and inert atmosphere at heating rates of 5, 7.5 and 10 °C min−1. The hemicellulose maximum mass loss rate was at 250 °C, cellulose at 330 °C and lignin decomposition from 190 to 500 °C, but the maximum mass loss rate at 430 °C, the devolatilization was at ~200 °C. The variation of apparent Eα represents single-step kinetics on the degradation process and OFW model is in better accordance with the experimental data and satisfactorily described the complexity of degradation process. SEM/EDX analyses showed carbon, oxygen, aluminum, magnesium and iron.
Keywords: Bioenergy; SEM/EDX; Sugarcane bagasse; Thermal analysis